Citizen science informs demand-driven breeding of opportunity crops - Voss, Rachel C.; De Sousa, Kaue; N'Danikou, Sognigbé; Shango, Abdul; Aglinglo, Lys Amavi; Laporte, Marie-Angelique; Legba, Eric C.; Houdegbe, Aristide Carlos; Diarra, Danfing dit Youssouf; Dolo, Aminata; Sidibe, Amadou; Ouedraogo, Colette Ouidyam; et al. (Wiley, 2025)
Amid global challenges of food insecurity, poor nutrition, and climate change, neglected crops like amaranth are gaining renewed attention. We studied farmers' preferences for amaranth varieties across diverse geographical contexts to guide targeted breeding. Our results revealed significant variation in farmer preferences, emphasizing the need for context‐specific breeding strategies. These findings can support the development of improved amaranth varieties that meet local needs, expand economic opportunities—especially for women—promote healthier diets, and boost biodiversity. This work also offers a model for participatory research on opportunity crops, informing inclusive agricultural policies and sustainable development strategies across Africa and beyond.Opportunity crops, also known as neglected and underutilized species (NUS), offer benefits to diversify food systems with nutritious and climate‐resilient foods. A major limitation to incorporating these crops in farming systems is the lack of improved varieties, which impedes farmers from accessing quality planting materials of these crops. The study explored how citizen science methods can support demand‐driven breeding and seed production of NUS using leafy amaranth – a nutritious and hardy vegetable ‐ as a case study. The study identified farmer preferences and market segments, with particular attention to gender and social differentiation. We used the tricot approach to conduct participatory on‐farm trials of 14 varieties with 2,063 farmers from Benin, Mali, and Tanzania. We then analyzed farmer traits and varietal preferences in aggregate and among segments of farmers, using cluster analysis. Farmers' overall preferences for amaranth varieties were driven principally by plant survival, yield, leaf size, taste, and marketability. Distinct farmer segments (older women generalists, young women specialists, older men generalists, and young men specialists) preferred different varieties depending on gender and business orientation. The identified farmer segments, along with their unique variety preferences, provide valuable information for breeders and seed enterprises, and support demand‐driven amaranth breeding and seed system development. The methods used and lessons learned from our citizen science exercise can be applied to enhance breeding and seed supply of other opportunity crops that are underutilized in Africa and elsewhere.Opportunity crops, also known as neglected and underutilized species (NUS), offer benefits to diversify food systems with nutritious and climate‐resilient foods. A major limitation to incorporating these crops in farming systems is the lack of improved varieties, which impedes farmers from accessing quality planting materials of these crops. The study explored how citizen science methods can support demand‐driven breeding and seed production of NUS using leafy amaranth – a nutritious and hardy vegetable ‐ as a case study. The study identified farmer preferences and market segments, with particular attention to gender and social differentiation.We used the tricot approach to conduct participatory on‐farm trials of 14 varieties with 2,063 farmers from Benin, Mali, and Tanzania. We then analyzed farmer traits and varietal preferences in aggregate and among segments of farmers, using cluster analysis.Farmers' overall preferences for amaranth varieties were driven principally by plant survival, yield, leaf size, taste, and marketability. Distinct farmer segments (older women generalists, young women specialists, older men generalists, and young men specialists) preferred different varieties depending on gender and business orientation.The identified farmer segments, along with their unique variety preferences, provide valuable information for breeders and seed enterprises, and support demand‐driven amaranth breeding and seed system development. The methods used and lessons learned from our citizen science exercise can be applied to enhance breeding and seed supply of other opportunity crops that are underutilized in Africa and elsewhere.